DISPOSITION OF CEFTRIAXONE (Ro 13-9904) IN RATS (III): BLOOD LEVEL PROFILES AND TISSUE DISTRIBUTION OF 14C-CEFTRIAXONE FOLLOWING REPETITIVE INTRAVENOUS ADMINISTRATION - TOMISAWA, HIROKI; ICHIHARA, SHIGEYASU; TAHARA, HITOSHI; TATEISHI, MITSURU; FUKAZAWA, HIDEO (CHEMOTHERAPY, 1984)
14C-ceftriaxone C-CTRX, (14C-Ro 13-9904) was consecutively given to both genders of rats for 14days at a daily intravenous dose of 20mg/kg. The blood concentration-time profiles of both 14C-radioactivity and the intact drug during the repetitive administration and the elimination of 14C from various tissues after a cessation of the drug were examined at the scheduled time points. 1. Blood level-time profile: The 14C-radioactivities in blood were likely to reach a steady state-level within 10 days. The 24-hr level on day 10 was 2-4 times as high as that on day 1. The blood concentrationtime profile of the intact drug was not significantly changed over the consecutive administration. 2. Accumulation of 14C-radioactivity into and its elimination from tissues: By the consecutive i.v. administration of 14C-CTRX to rats, the radioactivity was significantly accumulated into most of the tissues examined other than both gastrointestinal tract (including its contents) and brain; the 24-hr levels in each tissue after the last administration were 3-4 times higher than those at the 24th hr after a single i.v. administration (20 mg/kg). On day 10 after the withdrawal of the drug, the 14C-levels in all the tissues (except for thyroid gland, spleen and kidney) were not higher than the respective 24-hr levels observed in the single dose study, while for the 14C-levels in above three tissues it took 6 weeks to reach the 24-hr levels of the single administration. The intact drug was not accumulated in any tissues after the 14-days consecutive administration.